PENGARUH DPK, NPL, LDR DAN SUKU BUNGA KREDIT TERHADAP PENYALURAN KREDIT UMKM (STUDI PADA BPR DI KOTA SEMARANG TAHUN 2013-2016) - Farida Qusnul Khotimah; Suci Atiningsih (JURNAL STIE SEMARANG, 2018)
The study aims to determine the effect of third-party Funds (DPK)), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), and Loan Interest Rates to UMKM lending. This research is quantitative by using secondary data. The population in this study ias all Rural Banks (BPR) in Semarang City registered in the Financial Services Authority (OJK) for the period of 2013-2016. By using purposive sampling method, obtained a sample of 64 banks. This research use analysis tool that is doubled linear regression. The variables in this study consist of four independent variabels which include third-party Funds (DPK), Non Performing Loan (NPL), Loan to Deposit Ratio (LDR), Loan Interest Rate and one dependent variable UMKM credit distribution. Based on the results found that the DPK has a positive and significant impact on the credit distribution of UMKM, the NPL has no negative and significant impact on the lending of UMKM, the LDR has a positive and significant impact on the credit distribution of UMKM, and the Interest Rates has no negative and significant impact on the lending of UMKM.